2005
DOI: 10.1021/ol050195l
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Direct Intermolecular Aldol Reactions with Enantiotopic Group Selectivity and Dynamic Kinetic Resolution

Abstract: [reaction: see text] Proline-catalyzed aldol reactions of tetrahydro-4H-thipyranone with racemic 1,4-dioxa-8-thia-spiro[4.5]decane-6-carboxaldehyde and with meso/dl 1,4-dioxa-8-thiaspiro[4.5]decane-6,10-dicarboxaldehyde proceed with dynamic kinetic resolution and give single adducts in good yields with excellent ee's. The high enantiotopic group selectivity results from the high intrinsic diastereoface selectivity of the aldehydes. These reactions significantly extend the scope of the enantioselective direct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
35
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 42 publications
2
35
0
2
Order By: Relevance
“…15,16 Although this reaction provided 9a with high enantioselectivity (>98%ee), the yield still needed to be improved. Meticulous optimization showed that a large excess of ketone 7 (i.e.…”
mentioning
confidence: 99%
“…15,16 Although this reaction provided 9a with high enantioselectivity (>98%ee), the yield still needed to be improved. Meticulous optimization showed that a large excess of ketone 7 (i.e.…”
mentioning
confidence: 99%
“…[5] Dynamic kinetic resolutions based on organocatalysis are emerging as powerful and complementary approaches for the conversion of racemic substrates to products with high enantioselectivity. Organocatalytic DKRs have employed a wide variety of activation strategies, including Lewis bases, [6] hydrogen bond donors, [7] chiral Brønsted acids, [8] enamine/iminium ions, [9] and peptide-based biaryl oxidations. [10] While N-heterocyclic carbene (NHC) catalysis has been used in very few cases of traditional kinetic resolutions [11,12] or parallel kinetic resolutions, NHC-DKRs should provide significant new opportunities.…”
mentioning
confidence: 99%
“…In particular, they were used to develop methods for desymmetrization of cyclic meso-anhydrides [4], imides [5], and epoxides [6], asymmetric deprotonation of prochiral cyclic ketones [7], catalytic conjugate addition [8], stereoselective aldol reactions [9], etc. [10]. Chiral tertiary amines were also used: P,N-containing rhodium catalysts for asymmetric hydrogenation of olefins were described [11,12]; condensations of organometallic compounds with aldehydes, catalyzed by chiral tertiary amines were reported [13]; Sharpless osmium complexes based on quinine and cinchonidine catalyzed asymmetric dihydroxylation of olefins [14]; BaylisHillman reaction was performed in the presence of in this case the reaction was accompanied by formation of a considerable amount of nonpolar oxaziridine V as a mixture of diastereoisomer at a ratio of 4 : 1.…”
mentioning
confidence: 99%